Simple smartphone applications for superimposing 3D imagery in forensic dentistry - Haryono Utomo; Mieke Sylvia Margaretha Amiatun Ruth; Levina Gita Wangsa; Rodrigo Ernesto Salazar-Gamarra; Liciano Lauria Dib (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Forensic dentistry identification commonly involves using dental cast models as ante-mortem data. Here, dentists generally send the pictures as well as the dental records. However, in recent times, dentists – especially orthodontists and prosthodontists – are using 3D scanners in view of reducing the space for cast model storage as well as sending the 3D imaging for fabricating clear aligners and other items such as crowns and bridges. This new trend means data transmission and viewing has become more complicated since sophisticated laptops or personal computers are generally required. For more practical use, smartphones would be a better option, meaning various simple ideas for viewing 3D data must be explored. Furthermore, the conclusions must be evaluated in terms of the validity for forensic dentistry use. Purpose: To evaluate a number of smartphone applications that are simple, user friendly, scalable and capable of the measurement and superimposition of 3D imaging data. Review: Standard tessellation language (STL) is one of the 3D scan file formats that is also useful for 3D printing. Recently, several applications for 3D viewing have been made available for iPhones (iOS) and Android-based devices, which are able to view STL files. However, they have all received both positive and negative reviews in terms of various applications, including forensic dentistry, and they thus require further evaluation by forensic odontologists. Conclusion: Each application has advantages and disadvantages; however, in our experience as forensic odontologists, the CAD Assistant, exocad and Adobe Photoshop Mix, which are available for iOS and Android devices, are preferable for forensic dentistry needs